Prevalence and Epidemiological Variation of Oral Squamous Cell Carcinoma among Population of Central Nepal - Sharma, Sandeep (Journal of College of Medical Sciences-Nepal, 2019)
Background: Squamous cell carcinoma (SCC) is the most common malignant neoplasm of the oral cavity and represents about 90% of all oral malignancies. Oral squamous cell carcinoma (OSCC) is an important cause of morbidity and mortality worldwide with an incidence rate that varies widely by geographic location. The purpose of this study was to identify any trends in prevalence at specific anatomic sites or within specific age or sex groups of OSCCs in Chitwan population of Nepal. Methods: The study covers the period between January 2016 and October 2018. OSCC cases were retrospectively analysed for site, age, gender and habits and the findings were formulated to chart the trends in Chitwan population. Results: The study revealed a male to female ratio of 2.45:1 with the largest number of OSCCs developing in the fourth and fifth decades of life. Most commonly affected site was the buccal mucosa (66.06%), followed by retromolar area (19%), floor of the mouth (10.41%), lateral border of the tongue (1.81%), labial mucosa (2.26%), and palate (0.45%). Smokeless tobacco habit was more prevalent than smoking tobacco in both men as well as women. Chi Square test was done to show association between different variables i.e. between gender to site and gender to habit and gender to different grades of cancer, which were found to be non-significant. Conclusions: Oral cancer is an important cause of morbidity and mortality worldwide with an incidence rate that varies widely by geographic location. Even within one geographical location, the variations are seen among groups categorized by age, sex, site or habit.